If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -51 = 3x + -6(-1x + 25) Reorder the terms: -51 = 3x + -6(25 + -1x) -51 = 3x + (25 * -6 + -1x * -6) -51 = 3x + (-150 + 6x) Reorder the terms: -51 = -150 + 3x + 6x Combine like terms: 3x + 6x = 9x -51 = -150 + 9x Solving -51 = -150 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -51 + -9x = -150 + 9x + -9x Combine like terms: 9x + -9x = 0 -51 + -9x = -150 + 0 -51 + -9x = -150 Add '51' to each side of the equation. -51 + 51 + -9x = -150 + 51 Combine like terms: -51 + 51 = 0 0 + -9x = -150 + 51 -9x = -150 + 51 Combine like terms: -150 + 51 = -99 -9x = -99 Divide each side by '-9'. x = 11 Simplifying x = 11
| 15=5/3m | | 4x+33+x+37=180 | | 9(x)=15 | | 7(3x+9)/2=6(2x+31)/4 | | 5x-10y=-5 | | -6(x+7)=-90 | | 17-4*n=11+2*n | | 6/8=64 | | 3x-17y=11 | | 7x-3x-(10x+2)=5+x | | 12t^2-17t=5 | | 5+8n=50+.5n | | 2x+5y=6.25 | | 17-4n=11+2n | | 15x-4=3x+8 | | 7b+6=22 | | 4(6n-1)=164 | | 2x/9x-7 | | (12x+7)=(30x-4) | | 5a+9y=17 | | X^2-576=0 | | 1/5x+y=30 | | -28=-7x-2(-5x+23) | | 4(2-y)+3y=3(y-4) | | 16-8a=2a | | -11m+1=-10m+18 | | 8(7n-4)=-144 | | 8-n=3(2n-4) | | -11m+1=-10+18 | | -1/2(8x+2)+1/5(35x+10) | | 4b-7=20+4b | | (4u-5)(3+u)=0 |